KEARIFAN LOKAL DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH DASAR - Wati, Naurin Julia; Wahyuni, Arrum Dwi; Wulandari, Putri; Fikri, Rivaldi Aulia; Hariandi, Ahmad; Prishidayati , Prishidayati (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
The purpose of this study includes implementing local wisdom values in learning Islamic religious education in elementary schools. This research applies a descriptive qualitative approach. The data source consists of two types of informants, namely teachers of SDN 55/I Sridadi Islamic Religious Education (PAI) and students of SDN 55/I Sridadi, with the class as the main observation environment, as well as support from archives and documents related to this research. Data collection techniques are carried out by observation and document study. The results of the study can be concluded that the application of local wisdom values in Islamic Religious Education (PAI) learning, the steps that need to be taken include the selection of relevant learning materials, alignment with Islamic religious values, the use of interactive learning methods, local community involvement, collaborative projects with local communities, and organizing reflections and discussions. By implementing these measures in a structured manner, educational institutions can increase the linkage between Islamic religious lessons and local wisdom values, which in turn will play a positive role in the formation of the character and identity of students.